Israels Exil in Juda nach der Urfassung von 1-2Könige - Schütte, Wolfgang (Biblica, 2017)
The Old Latin manuscript L 115 is considered in this article as representing the oldest (pre-exilic) form of 1-2 Kings and this for reasons based on its content. In this version, 2 Kings 17 takes a critical stand with respect to the religious situation of the Israelites in the land of Judah where they had fled after the fall of Samaria in 722 BCE.